Adrenal function in man height, sensitivity to ACTH - Silva Reaño, Cecilia (1958)
In 21 medical students from Lima, and 15 native residents Morococha (4.540 meters), in good health, and 20 to 30 years of age, a study of the adrenal sensitivity to ACTH is performed by administering 2 and 5 UI ACTH as described for the standard test. Eosinophil counts and urine tests for total neutral 17 ketosteroids and 17 total hydroxycorticoids are made.